JURIDICAL ANALYSIS OF THE ROLE OF COMMUNITY ADMINISTRATION FOR THE RECOVERY OF UNDERAGE CHILDREN DUE TO BREACHING OF LAW TO REALIZE THE CONSTITUTIONAL RIGHTS OF CHILDREN - Zulin. H, Agi (RADJA PUBLIKA, 2022)
The role of community mentors for the recovery of minors due to violations of the law to realize the constitutional rights of children is a paradigmatic key to the correctional system. The problems that will be researched and analyzed are how the legal arrangements, implementation, and what factors become obstacles and solutions to community mentors for the recovery of minors due to violations of the law to realize the constitutional rights of children. Methods of data collection in this research using library research and field studies. Data analysis used qualitative analysis. this type of research uses normative law research and is supported by empirical law research. The results of this legal research reveal that community advisors make the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System and Government Regulation of the Republic of Indonesia Number 65 of 2015 concerning Guidelines for the Implementation of Diversion and Handling of Children under 12 (twelve) years old, very important in determining the future fate of children. The role of community counselors as researchers, mediators, mentoring, mentoring and supervision of children dealing with the law while serving a sentence. Barriers to lack of human resources, limited facilities and infrastructure, lack of coordination of law enforcement, family conditions, personal factors, low education of children, and environmental influences. Solutions to increase human resources, excess facilities and infrastructure, the creation of law enforcement coordination, children's family conditions, increasing knowledge for themselves, increasing children's education, and environmental influences. It is hoped that legal arrangements can run well, community supervisors prioritize the best interests in accordance with applicable law, and continue to provide support to children in order to create justice, certainty and benefit for children for the best future.